Building the right centriole for each cell type - Loncarek, Jadranka (2017)
The centriole is a multifunctional structure that organizes centrosomes and cilia and is important for cell signaling, cell cycle progression, polarity, and motility. Defects in centriole number and structure are associated with human diseases including cancer and ciliopathies. Discovery of the centriole dates back to the 19th century. However, recent advances in genetic and biochemical tools, development of high-resolution microscopy, and identification of centriole components have accelerated our understanding of its assembly, function, evolution, and its role in human disease. The centriole is an evolutionarily conserved structure built from highly conserved proteins and is present in all branches of the eukaryotic tree of life. However, centriole number, size, and organization varies among different organisms and even cell types within a single organism, reflecting its cell type-specialized functions. In this review, we provide an overview of our current understanding of centriole biogenesis and how variations around the same theme generate alternatives for centriole formation and function.